Analysis Effect of Productive Zakat on The Welfare Mustahiq Through Development of Micro (A Case Study at Badan Amil Zakat (BAZNAS), Yatim Mandiri, and LAZIS-NU Tulungagung in East Java) - Nurkartikasari, Rizky; Muljaningsih, Sri; Ekawaty, Marlina (AIBPM Publisher, 2023)
The purpose of this study is to determine the influence of productive zakat on mustahik welfare through the development of micro businesses in the National Amil Zakat Agency (BAZNAS), Yatim Mandiri, and LAZIS-NU Tulungagung Regency East Java, and also to determine the influence of micro business development on mustahiq welfare.This study uses quantitative methods with an explanatory or confirmatory approach, namely to get an explanation of the relationship betweenÂ variables, and using PLS (Partial Least Square) approach analysis. The objects in this study are productive zakat, the development of micro-enterprises, and mustahiq welfare. The results of the study showed that productive zakat had an effect on the development of micro enterprises, while productive zakat did not affect the welfare of mustahiq, and finally the development of micro enterprises did not affect welfare.